2016
DOI: 10.1027/1618-3169/a000331
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Configural Learning of Non-Linear Discriminations and Detection of Stimulus Compounds

Abstract: Previous work showed that prior experience with discriminations requiring configural solutions (e.g. biconditional discrimination) confers an advantage for the learning of new configural discriminations (e.g. negative patterning) in comparison to prior experience with elemental discriminations. This effect is well established but its mechanism is not well understood. In the studies described below we assessed whether the saliences of configural and element cues were affected by prior training. We observed posi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Similar to previous studies [12,13,26,30], our results suggest that configural processing is flexible and increases after exposure to configural discriminations. This flexibility is thought to be advantageous, as it allows individuals to adapt their processing style depending on which strategy is more useful for learning contingencies between stimuli in the environment.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to previous studies [12,13,26,30], our results suggest that configural processing is flexible and increases after exposure to configural discriminations. This flexibility is thought to be advantageous, as it allows individuals to adapt their processing style depending on which strategy is more useful for learning contingencies between stimuli in the environment.…”
Section: Discussionsupporting
confidence: 91%
“…If so, it would mean that fluid abilities not only influence generalization strategies in ambiguous situations (e.g., on a transfer test in which participants are asked to predict the outcome to a combination of cues they have never experienced) but also in unambiguous situations in which participants receive feedback. Indeed, it is known that learning to solve one discrimination influences performance on a subsequent discrimination [12,13,14]. Our aim was to investigate the role of fluid abilities on the extent to which learning one discrimination influences the acquisition of new discriminations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it has often been observed that previous experience solving a discrimination in which a configural solution is necessary, facilitates solving a second discrimination with a configural requirement (Glautier et al, 2016; Mehta & Russell, 2009). Therefore, previous experience solving a discrimination modulates subsequent behavior (i.e., transfers) concerning new discriminations (Urcelay & Miller, 2010).…”
mentioning
confidence: 99%